2014
DOI: 10.1097/01.pra.0000456590.12998.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregabalin Augmentation in Treatment of Patients with Combat-Related Chronic Posttraumatic Stress Disorder

Abstract: Pregabalin effectively reduced the severity of PTSD symptoms but it was not effective in improving the severity of depression, anxiety, and quality of life. Further investigations are required to confirm or refute these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Pregabalin (PGB), a gabapentinoid derivative of γ-aminobutyric acid, possesses the potential to positively affect neurobehavioral changes associated with PTSD. Baniasadi et al ., found that pregabalin used as an adjunct to traditional treatments, effectively reduced the severity of PTSD symptoms in patients diagnosed with chronic PTSD [19]. This study of 37 adult male patients specifically examined a post-exposure treatment model.…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin (PGB), a gabapentinoid derivative of γ-aminobutyric acid, possesses the potential to positively affect neurobehavioral changes associated with PTSD. Baniasadi et al ., found that pregabalin used as an adjunct to traditional treatments, effectively reduced the severity of PTSD symptoms in patients diagnosed with chronic PTSD [19]. This study of 37 adult male patients specifically examined a post-exposure treatment model.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies assessed risperidone (Bartzokis et al, 2005;Hamner et al, 2000;Krystal et al, 2011;Monnelly et al, 2003;Reich et al, 2004;Rothbaum et al, 2008), three assessed topiramate (Akuchekian & Amanat, 2004;Batki et al, 2014;Lindley et al, 2007), and two assessed d-cycloserine (Attari et al, 2014;Heresco-Levy et al, 2002). There were single studies assessing aripiprazole (Naylor et al, 2015), baclofen (Manteghi et al, 2014), bupropion (Becker et al, 2007), eszopiclone (Pollack et al, 2011), guanfacine (Neylan et al, 2006), hydrocortisone (Ludascher et al, 2015), mirtazapine (Schneier et al, 2015), nabilone (Jetly et al, 2015), olanzapine (Stein et al, 2002), pregabalin (Baniasadi et al, 2014), sodium valproate (Hamner et al, 2009) and ziprasidone (Ramaswamy et al, 2016). The average duration of studies was 10.5 (±5.6) weeks, with an average age of 44.6 (±7.7) years and a mean sample size of 52.2 (±66.1) participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Characteristics of 2,331 adult patients from published doubleblind, parallel 36 RCTs (Frank et al, 1988;Davidson et al, 1990;Kosten et al, 1991;Hertzberg et al, 2000;Stein et al, 2002;Zohar et al, 2002;Hamner et al, 2003;Monnelly et al, 2003;Akuchekian & Amanat, 2004;Chung et al, 2004;Davis et al, 2004;Bartzokis et al, 2005;Neylan et al, 2006;Friedman et al, 2007;Lindley et al, 2007;Raskind et al, 2007;Davis et al, 2008a;Davis et al, 2008b;Hamner et al, 2009;Krystal et al, 2011;Panahi et al, 2011;Germain et al, 2012;Litz et al, 2012;Baniasadi et al, 2014;Batki et al, 2014;Manteghi et al, 2014;Rothbaum et al, 2014;Naylor et al, 2015;Back et al, 2016;Petrakis et al, 2016;Rodgman et al, 2016;Villarreal et al, 2016;Ramaswamy et al, 2017;Rezaei Ardani et al, 2017;Surís et al, 2017;Raskind et al, 2018) were described in the study. Among them, three studies (Frank et al, 1988;Kosten et al, 1991;Rothbaum et al, 2014) reported active-comparator experiments.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among them, three studies (Frank et al, 1988;Kosten et al, 1991;Rothbaum et al, 2014) reported active-comparator experiments. Our research involves a variety of drug types, including atypical antipsychotics (AASs) (Stein et al, 2002;Monnelly et al, 2003;Bartzokis et al, 2005;Hamner et al, 2009;Krystal et al, 2011;Naylor et al, 2015;Villarreal et al, 2016), corticosteroids (Surís et al, 2017), alpha blockers (Raskind et al, 2007;Germain et al, 2012;Petrakis et al, 2016;Rodgman et al, 2016;Raskind et al, 2018), anticonvulsants (Hamner et al, 2003;Akuchekian & Amanat, 2004;Lindley et al, 2007;Davis et al, 2008a;Batki et al, 2014), central muscle relaxants (Manteghi et al, 2014), D-cycloserine (Litz et al, 2012;Rothbaum et al, 2014), N-acetylcysteine (Back et al, 2016), γ-aminobutyric acid (Baniasadi et al, 2014), reversible cholinesterase inhibitor (Rezaei Ardani et al, 2017), serotonin antagonist and reuptake inhibitors (SARIs) (Davis et al, 2004); SSRIs (Hertzberg et al, 2000;Zohar et al, 2002;Friedman et al, 2007;Panahi et al, 2011;Ramaswamy et al, 2017), tricyclic antidepressants (TCAs) (Frank et al, 1988;Davidson et al, 1990;Kosten et al, 1991), α2 receptor agonist…”
Section: Study Characteristicsmentioning
confidence: 99%